PENGARUH MOTIF PENGGUNAAN MEDIA INTERNAL EXCELLENCE TERHADAP KEPUASAN INFORMASI KARYAWAN PERSEROAN TERBATAS (PT) BANK RIAU KEPRI PEKANBARU - Yesi Tri Amalia; W.E Tinambunan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research aims to provide an understanding about motive in using “Excellence” (an internal media) to the employee information satisfaction at Bank Riau-Kepri Pekanbaru Branch, and also to find out the favourite category for “Excellence” readers. Corporate Secretary; as a part of editorial team; has important role in engaging communication to the all employees that are widely spread at Riau and Kepulauan Riau Province. Moreover, Corporate Secretary should also have knowledge about reader motives so that “Excellence” can deliver appropriate content that can give information satisfaction to the readers. Quantitative research method was used to find out: (a) significant relation between motives in using Excellence to the employee satisfaction at Bank Riau-Kepri Pekanbaru Branch, and (b) “Excellence” reader favourite category. In order to meet these objectives, two approaches were followed; questionnaire and library studies. Later, data gathered from these questionnaires were then analysed by Simple Linear Regression method using commercial statistical software SPSS version 16.0. Result revealed that there was a significant correlation between motive and the use of “Excellence” to the employee satisfaction at Bank Riau-Kepri Pekanbaru Branch. With amount of observation (N)=70, simple Linear Regression analysis resulted a formulation of Y=20.439+0.433X. Included in this output were be (a) t=3.221, which was higher than that of “constant” in the SPPS output t=1.668, and (b) significant (a)=0.002 which was less than that of constant SPSS output a=0.1. It was concluded that correlation between motive and the use of “Excellence” was at low level, 13.2%. Regarding to the categories in “Excellence”, survey showed that 81% of respondent population chose photo gallery as their most favourite one. Keywords: Media Internal, Motif, Kepuasan